Neoliberalismo e desdemocratização: o novo eixo dos estudos políticos? - Rocha, Thainara de Ávila (2022)
Pursuing to identify the existence of a new research axis in the Political Science, on this body of work we are analyzing the theories that deal with the democratic decline in the last decade. This analysis is based on the the fiscal relations, understanding that these are capable of creating subjectivities and changing the history of countries. On that matter, we explore the relationship between neoliberalism and the democratic decline. On these theories, which have distinct approaches, we found a concatenation between the way that democracy progressively fades alongside the consolidation of neoliberalism policies around the globe.